Atlas de los vertebrados inferiores de la Región de Cuyo - Cei, José Miguel Alfredo María (1978)
The geographical and altimetric distribution of Amphibians, Reptiles and Fishes from the Andean and Subandean regions of Cuyo —Mendoza and San Juan provinces— is summarized in 30 representative maps. The patterns, of species distribution are shown by symbols which point out localities or limited areas;where' specimens or samples have been collected, and photographic or ecological records registered. Short indicative notes emphasize the most important biogeographical traits of the yet reported 9 species of Amphibians, 55 species and subspecies of Reptiles, and 10 species of Fishes. The collections of the Instituto de Biologfa Animal of the Universidad Nacional de Cuyo, Mendoza, and those of the Museo de Historia Natural of the city of San Rafael, Mendoza State, are the basic information sources of maps and reports«